Tunable hydrogen evolution activity by modulating polarization states of ferroelectric BaTiO3. Issue 13 (13th March 2023) - Qiu, Haifa; Yang, Tong; Zhou, Jun; Yang, Ke; Ying, Yiran; Ding, Keda; Yang, Ming; Huang, Haitao
Abstract : We computationally reveal that HER activity on BTO is governed by polarization states, being optimal with in-plane polarization. A strain driven HER cycle on BTO between downward and in-plane polarization is proposed to overcome the Sabatier limit. Abstract : Switchable polarization in ferroelectric catalysts shows promise to overcome the Sabatier limit imposed on traditional catalysts. However, a comprehensive understanding of the polarization effect on electrocatalytic performance remains elusive. In this study, using ferroelectric BaTiO3 (BTO) as a model system, we report tunable hydrogen evolution reaction (HER) performance governed by polarization states. Based on first-principles calculations, we find that BTO with in-plane polarization shows improved HER activity, in contrast to that with out-of-plane polarization, which is linked to in-plane dipole–dipole interaction at the surface. Interestingly, surface rumpling induced by surface relaxation and polarization states plays an important role in determining surface polarization, which significantly affects the chemical reactivity of surface oxygen. We unravel that the favorable p-band center of surface oxygen is responsible for the enhanced HER activity of in-plane polarized BTO. We further propose the HER catalytic cycle at the BTO surface to break the Sabatier limit via applying controllable polarization states. This work provides an inspiring insight into tunable ferroelectric catalysis by modulating polarization states toward robust HER and beyond.